Analysis of Early Given Breast Milk Complementary Foods in Baby Age 0-6 Month at Larangan Health Public Center in Health Departement of Pamekasan - Nur Khalilah; Nurwijyanti Nurwijyanti; Nurdina Nurdina (Journal for Quality in Public Health, 2018)
Breast Milk Complementary Foods (MP-ASI) is a supplementary food given to infants other than breast milk after 6 months of age until the age of 24 months. Breast milk complementary foods is given to meet the energy and nutrient needs of infants that are not covered by breast milk. the factors that are suspected to be the cause of mother giving ASI AS early are knowledge, social economy, culture and health cadre role. The purpose of this study was to analyze the factors that influence the provision of early given Breast milk complementary foods in infants aged 0-6 months. The type of this research is quantitative research with analytic observational design with cross sectional. This study was conducted from February to March 2018 at Larangan Health Public Center of Pamekasan with a population of mothers who have babies 0-6 months who provide early Breast milk complementary foods of 86 people. The sample size was 71 respondents, with sampling accidental sampling type. The independent variables are knowledge, socioeconomic, cultural and health cadre's role. The dependent variable is the provision of early Breast milk complementary foods in infants aged 0-6 months. Data were collected using questionnaires. Data were analyzed using test logistic regression with α = 0.05. The results showed that the variable X1 (knowledge) with p = 0.035; OR = 3,725, variable X2 (social economy) p = 0,135; OR = 4,226, X3 (culture) p = 0,003; OR = 9,973, X4 (role of health cadre) p = 0,134; OR = 2, 187. So it can be concluded that the factors that affect Y (provide early Breast milk complementary foods in infants aged 0-6 months) are cultural and knowledge factors, with the most dominant factor is cultural factor with influence of 9.973. Social culture or tradition has a relationship with the provide early Breast milk complementary foods. The mindset of most people still trust it can accelerate the growth of babies by follow the tradition as a adherence to parents. So it can affect the knowledge, perception, and attitudes of a person to something, therefore need more intense health promotion efforts again in order to exclusive coverage of exclusive breastfeeding increases.